2017
DOI: 10.1111/1751-7915.12595
|View full text |Cite
|
Sign up to set email alerts
|

Statistical test for tolerability of effects of an antifungal biocontrol strain on fungal communities in three arable soils

Abstract: SummaryA statistical method was developed to test for equivalence of microbial communities analysed by next‐generation sequencing of amplicons. The test uses Bray–Curtis distances between the microbial community structures and is based on a two‐sample jackknife procedure. This approach was applied to investigate putative effects of the antifungal biocontrol strain RU47 on fungal communities in three arable soils which were analysed by high‐throughput ITS amplicon sequencing. Two contrasting workflows to produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Consistent with previous report that microbial community in rhizosphere could be shaped by microbiota in bulk soil (de Ridder‐Duine et al ., ), our result also revealed that the variation of soil microbiome in bulk soil could still exhibit a strong effect on rhizosphere microbial community. Unlike previous study that direct application of antifungal biocontrol strain into soil displayed a minor effect on fungal communities (Antweiler et al ., ), biofertilizer applied to fumigated soil displayed a strong influence on bacterial community composition both in bulk and rhizosphere soil even after banana re‐planted for couple of months. Thus, manipulation of the disturbed microbial community in bulk soil through lime and ammonium carbonate fumigation followed by biofertilizer application could assemble a healthy rhizosphere microbiome suppressive to banana Panama disease.…”
Section: Discussionmentioning
confidence: 93%
“…Consistent with previous report that microbial community in rhizosphere could be shaped by microbiota in bulk soil (de Ridder‐Duine et al ., ), our result also revealed that the variation of soil microbiome in bulk soil could still exhibit a strong effect on rhizosphere microbial community. Unlike previous study that direct application of antifungal biocontrol strain into soil displayed a minor effect on fungal communities (Antweiler et al ., ), biofertilizer applied to fumigated soil displayed a strong influence on bacterial community composition both in bulk and rhizosphere soil even after banana re‐planted for couple of months. Thus, manipulation of the disturbed microbial community in bulk soil through lime and ammonium carbonate fumigation followed by biofertilizer application could assemble a healthy rhizosphere microbiome suppressive to banana Panama disease.…”
Section: Discussionmentioning
confidence: 93%
“…Barcode, primer and adapter trimming were performed based on a customized in-house perl script including the FASTX toolkit 5 followed by raw sequence merging using FLASH ( Magoč and Salzberg, 2011 ). Subsequently, the analysis of the resulting sequences was carried out with a local version of the GALAXY Bioinformatics Platform 6 based on a database-dependent strategy ( Antweiler et al, 2017 ) using UNITE database v7.2 ( UNITE Community, 2017 ) by applying the closed reference approach ( Carter et al, 2017 ). All sequences were aligned with the database (e-value 0.001) and only results with an alignment length >200 bp and a similarity >97% to the reference were kept.…”
Section: Methodsmentioning
confidence: 99%
“…All sequences were aligned with the database (e-value 0.001) and only results with an alignment length >200 bp and a similarity >97% to the reference were kept. Furthermore, BLAST-PARSER ( Antweiler et al, 2017 ) was used for taxonomic assignment based on the lowest e-value. The fungal OTU abundance table was generated by counting the sequences per assignment and using the SH-numbers from the database as identifier.…”
Section: Methodsmentioning
confidence: 99%
“…Taxonomic affiliations were assigned by BlastN against the Silva SSU 128 database ( Quast et al, 2013 ). De-replication, singleton removal and clustering of sequences to operational taxonomic units (OTUs, >99% similarity) were performed using BLAST Parser ( Antweiler et al, 2017 ) implemented in a Galaxy workflow ( Cock et al, 2013 ). The multivariate analyses on the OTU abundance table were carried out with the R software version R3.1.3 2 with the packages vegan ( Oksanen et al, 2015 ), EdgeR ( Robinson et al, 2010 ), and LabDSV ( Roberts, 2016 ).…”
Section: Methodsmentioning
confidence: 99%